Influence of Interfacial Bonding between Metal Droplets on Tensile Properties of 7075 Aluminum Billets by Additive Manufacturing Technique. Issue 5 (May 2016) - Zuo, Hansong; Li, Hejun; Qi, Lehua; Zhong, Songyi
Abstract : 7075 aluminum billets were fabricated by micro droplet deposition manufacturing technique, and the influence of interfacial bonding between metal droplets on the tensile properties was studied. Three sets of samples were manufactured under different temperature conditions, and their mechanical properties were compared. The results show that the temperature of the metal droplets and substrate significantly affect the tensile strength of the sample. Moreover, with proper temperature setting, the 7075 aluminum billets manufactured by micro metal droplet deposition could achieve very good mechanical properties with a tensile strength of 373 MPa and an elongation of 9.95%, which are very similar to those of an extruded sample. Moreover, a metallurgical bonding diagram based on numerical calculations of interfacial temperature was established to predict the interfacial bonding state. In addition, the fracture morphologies of these specimens were observed. It is indicated that there was a significant transformation of failure mechanism with the improvement of metallurgical bonding, which agreed well with the numerical results.